A variability taxonomy to support automation decision-making for manufacturing processes. Issue 5 (3rd April 2020) - Goh, Yee Mey; Micheler, Simon; Sanchez-Salas, Angel; Case, Keith; Bumblauskas, Daniel; Monfared, Radmehr
Abstract: Although many manual operations have been replaced by automation in the manufacturing domain in various industries, skilled operators still carry out critical manual tasks such as final assembly. The business case for automation in these areas is difficult to justify due to increased complexity and costs arising out of process variabilities associated with those tasks. The lack of understanding of process variability in automation design means that industrial automation often does not realize the full benefits at the first attempt, resulting in the need to spend additional resource and time, to fully realize the potential. This article describes a taxonomy of variability when considering the automation of manufacturing processes. Three industrial case studies were analyzed to develop the proposed taxonomy. The results obtained from the taxonomy are discussed with a further case study to demonstrate its value in supporting automation decision-making.